ABUYA DIMYATI’S IDEA IN DEVELOPMENT OF TRADITIONAL ISLAMIC STUDIES AND SPIRITUALISTIC: STUDIES AT PONDOK PESANTREN CIDAHU PANDEGLANG - Fauzi, Anis (LPPM IAIN Kudus, 2017)
This study aims to understand deeply to the idea of Abuya Dimyati in development traditional Islamic educational and spiritualistic, so it produces an image of a well-organized and complete. This research uses descriptive method with the intention of collecting information about the status of existing symptoms, using the method of observation, interviews and documentation. The techniques in data collection used guidelines of observation, interview guidelines, and documentation guidelines. The results showed that: First, idea of Abuya Dimyati in development of traditional Islamic studies at boarding school of Cidahu Pandeglang basically more emphasis on textual understanding. The approach used is more oriented towards the reading completion of a book and then move to the next book so that the curriculum is not classical. Second, idea of Abuya Dimyati in development of spiritualistic studies at boarding school of Cidahu Pandeglang more emphasis on the teaching of tarekat (wirid), Abuya zikr using Tarekat al-Qodiriyyah, an-Naqsyabandiyyah, al-Khalwatiyah, and asy-Syadziliyyah.